Precipitation polymerization in liquid crystals to prepare uniform epoxy microspheres. (10th October 2018) - Chen, Mei; Liang, Xiao; Hu, Wei; Zhang, Lanying; Zhou, Le; Zhang, Cuihong; Wang, Junming; Meng, Chuizhou; Fang, Jingang; Yang, Huai
Abstract: In this paper, uniform epoxy resin polymer microspheres (EMs) with controllable diameters and a narrow size distribution were prepared by precipitation polymerization using liquid crystals (LCs) as the solvent. The effects of the LC solvents on the morphologies of the resultant epoxy resin were thoroughly investigated. It was found that the formation of uniform EMs is sensitive to the properties of the LCs solvents. Uniform EMs can be obtained when the solubility parameters ( δ ) of the used solvent range from 20.59 to 21.29 (cal/cm 3 ) 1/2 and its dispersion terms ( δ d ) are in the range of 19.87–20.89 (cal/cm 3 ) 1/2 . Apart from the effects of solvents, the size of the as-made EMs can be further regulated from 2.6 μm to 10.1 μm by controlling the reactivity of epoxy monomers and the functionality of thiol hardeners. Moreover, we demonstrated that carbonizing the EMs can directly produce uniform carbon microspheres (CMs) with smooth surface. This work enlightens a new way for the preparation of EMs through precipitation polymerization in LCs solvent. Graphical abstract: Highlights: The preparation of polymer microspheres in a LC solvent and a subsequent pyrolysis for carbon microspheres were reported. The effect of LC solvents on the formation of uniform polymer microspheres was estimated by solubility parameters. The diameters of the polymer microspheres can be regulated from 2.6 μm to 10.1 μm by controlling the compositions.